Types Of Service Industry Managers in The Sports Industry - Khudayberdiyeva Dilafruz Abidovna (Zien Journals, 2021)
This article contains theoretical considerations about the development of management in sports, the lack of highly qualified and experienced specialists in physical culture, the development and expansion of sports sections and directions, as well as the functions and principles of sports management.
Keywords: Modern Science; Service Industry; Sport; Manager